Anrio Sappara as Spiritual Coping within Selayar Community: A Multicultural Counseling Analysis Based on Pargament’s Psychology Framework - Syarip, Lutfiah; Aswar, Aswar (International Journal of Multicultural Counseling and Development, 2025)
Local wisdom plays a crucial role in shaping individual mindsets, behaviors, and psychological resilience. Within the Selayar community, the Anrio Sappara tradition serves as a form of spiritual coping that helps individuals manage psychological stress through prayer, remembrance, self-purification, and collective cleansing rituals. This paper examines how multicultural Guidance and Counseling can interpret and support this cultural practice using Pargament’s psychological framework. A literature review method was employed, analyzing nine relevant scholarly articles. The findings indicate that integrating local wisdom, spiritual coping, and multicultural counseling approaches enables counselors to provide culturally sensitive and contextually meaningful services. Such integration strengthens psychological well-being, supports cultural identity, and enhances the relevance of counseling interventions for the Selayar community. The study highlights the importance of culturally grounded counseling practices as a pathway to promoting holistic well-being.